IN EDUCATION OF STUDENTS CREATIVITY ACTIVITY IMPROVEMENT - Charos Babayorova; Abdunabiyev Jonibek; Tapkanov Diyorbek; Sherzodkhuja Mirzakhodjaev ("Science Shine" International scientific journal, 2024)
Abstract: In the article common medium education in their schools technology innovative pedagogy in the creative activity of students in science classes labor related to making simple items through the use of technology form skills and direct them to consciously choose a profession educational and educational importance illuminated.